Efektifitas Beberapa Variasi Waktu Tinggal Pengolahan Limbah Cair Industri Tahu dengan Menggunakan Biostarter ”X” Terhadap Penurunan BOD - Febrinaldy Syafni; Sri Puji Ganefati; Siti Hani Istiqomah (Poltekkes Kemenkes Yogyakarta, 2014)
Because their activities need water, beside producing specific products, some industries also yielding waste water as by-product whose quantity will corresponds with the quantity of the raw water. If the waste water is directly discharged into the environment without appropriate treat-ments, it will causing environmental pollution. Based on the preliminary test results, the level of BOD in the waste water effluent of the Central Tofu Industry in Trunan Village in Magelang were measured as much as 1259 mg/l and 860 mg/l, and so that, had not fulfilled yet the threshold ruled by the government of Central Java Province, i.e. 150 mg/l. One of the methods which can be used to process the waste water is by applying biostarter containing microorganisms for de-grading the existing organic substances. The study was aimed to determine the differrence of the reduction of BOD level resulted from three different detention times in the waste water treat-ment using biostarter “X”, through conducting a laboratory scaled pre-test post-test designed experiment. 15 tofu industries were sampled by using simple random technique, while the waste water sample from those industries were obtained by following the standard procedure. In each observed detention time, five different industries were placed. The results showed that the de-tention time of 7, 8 and 9 days, were able to decrease BOD level in the average of 27,0 %, 59,9 %, and 76,9 % respectively. One way anova test at 95 % significance level confirmed that the differences were significant, and the subsequent LSD test found that 9 day detention time was the most effective method. Further study for gaining more applicability of the study results is suggested to conduct a real field-scaled experiment.